Through-space transfer of chiral information mediated by a plasmonic nanomaterial - Ostovar pour, Saeideh; Rocks, Louise; Faulds, Karen; Graham, Duncan; Parchaňský, Václav; Bouř, Petr; Blanch, Ewan W (Nature chemistry, 2015)
The ability to detect chirality gives stereochemically attuned nanosensors the potential to revolutionize the study of biomolecular processes. Such devices may structurally characterize the mechanisms of protein-ligand binding, the intermediates of amyloidogenic diseases and the effects of phosphorylation and glycosylation. We demonstrate that single nanoparticle plasmonic reporters, or nanotags, can enable a stereochemical response to be transmitted from a chiral analyte to an achiral benzotriazole dye molecule in the vicinity of a plasmon resonance from an achiral metallic nanostructure. The transfer of chirality was verified by the measurement of mirror image surface enhanced resonance Raman optical activity spectra for the two enantiomers of both ribose and tryptophan. Computational modelling confirms these observations and reveals the novel chirality transfer mechanism responsible. This is the first report of colloidal metal nanoparticles in the form of single plasmonic substrates displaying an intrinsic chiral sensitivity once attached to a chiral molecule.
Keywords: Computer Simulation; cirkulární dichroismus; nanostruktury; Models, Molecular; Nanostructures; Stereoisomerism; počítačová simulace; molekulární modely; Surface Plasmon Resonance; Circular Dichroism; povrchová plasmonová rezonance; stereoizomerie